Modular Distance Learning: Its Challenges on Teachers’ Teaching Practices - Minangoao P. Imam (International Journal of Progressive Research in Science and Engineering, 2024)
The study aspires to determine the challenges encountered by the teachers from MSU – Lanao National College of Arts and Trades during the use of Distance Learning Modality throughout the time of Pandemic. The study used descriptive research design since it is flexible to gather information on the challenges encountered by the respondents. A self-made survey-questionnaire crossed-checked by the experts was used as primary research instrument because it is cost-effective and it involves a series of easy to answer questions using 5-point Likert scale to choose from. The survey-questionnaire consist of two parts. Part one, the demographic profile of respondents in terms of: Age, employment status, highest educational attainment and year in service. Part two, challenges encountered by the teacher during the Modular distance in terms of: preparation of modules, distribution, retrieving, checking and evaluating the learners’ response on the module and monitoring learners’ learning. The respondents grasped the selected thirty-two teachers MSU – Lanao National College of Arts and Trades as respondents of the study. The statistical tools used were frequency and percentage, weighted arithmetic mean and standard deviation. These statistical tools help with data sorting and help identify the remedies on issues regarding the use of distance learning modality. Moreover, the results revealed that the respondents encountered various problems in teaching during pandemic. One issues encountered towards distance learning approach were communication failure on instructions or puzzlement of learners on the modules, limited teachers’ guidance, learners’ in ungracious approach to teachers, troubles on not understanding the module, and all of which resulted to misbehavior. Additionally, teachers also lack of knowledge, skills and devices, internet connection.